Finite element analysis for design engineers - Kurowski, Paul M. (Society of Automotive Engineers. Electronic publications., 2017)
This indispensable guide provides design engineers with proven methods to analyze their own work while it is still in the form of easily modifiable CAD models. Simple and informative exercises provide examples for improving the process to deliver quick turnaround times and prompt implementation.